1970
DOI: 10.1172/jci106408
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics, coronary blood flow, and myocardial metabolism in coronary shock; response to l-norepinephrine and isoproterenol

Abstract: A B S T R A C T Hemodynamics and myocardial metabo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

1971
1971
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(24 citation statements)
references
References 64 publications
3
20
0
1
Order By: Relevance
“…Studies were not performed when these measurements could not be stabilized. Temporal variations of myocardial metabolism in coronary shock were presented previously, demonstrating that a relatively steady state had been achieved and confidence limits had been established, to judge the effect of therapeutic interventions (32). The patients treated with IACP were similar to those previously reported.…”
Section: Experimental Protocolsupporting
confidence: 71%
“…Studies were not performed when these measurements could not be stabilized. Temporal variations of myocardial metabolism in coronary shock were presented previously, demonstrating that a relatively steady state had been achieved and confidence limits had been established, to judge the effect of therapeutic interventions (32). The patients treated with IACP were similar to those previously reported.…”
Section: Experimental Protocolsupporting
confidence: 71%
“…In those 10 animals in which isoproterenol was infused for less than 30 min, final measurements were recorded [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] '3M Co., St. Paul, Minn. min after discontinuation of isoproterenol. Then, the animals were anesthetized with 30 mg/kg pentobarbital sodium, and sacrificed to confirm placement of intramyocardial transducers and to obtain myocardial samples at the same sites for regional blood flow determination.…”
Section: Methodsmentioning
confidence: 99%
“…15 Ten of 11 patients treated with isoproterenol alone, l-norepinephrine alone, or with both agents died during their initial hospitalization. Three of these patients lived longer than 3 days, and the survival time of the entire group who died in the hospital ranged from none to 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…4 11-16 Previous studies from our laboratory demonstrated striking differences in cardiac performance and metabolism among the various types of shock and suggested that pharmacologic therapy should be based on metabolic abnormalities of the myocardium. 15 This study was undertaken to determine whether either isoproterenol or l-norepinephrine could improve myocardial metabolism and performance in coronary shock. Selection of any existing pharmacologic agent may well involve a compromise since improvement of cardiac function is achieved at the expense of increased cardiac work.…”
mentioning
confidence: 99%